2009
DOI: 10.1007/s10608-009-9261-y
|View full text |Cite
|
Sign up to set email alerts
|

Dimensions of Negative Thinking and the Relations with Symptoms of Depression and Anxiety in Children and Adolescents

Abstract: The current study sought to examine three forms of negative, repetitive thinking in non-clinical children and adolescents aged between 10 and 18. More specifically, this study addressed the degree to which stress-reactive rumination can be differentiated from other forms of repetitive thinking, such as emotion-focused rumination and worry, and the associations between the various indices of repetitive thinking and symptoms of anxiety and depression. Participants completed a battery of self-report questionnaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(54 citation statements)
references
References 48 publications
5
45
1
3
Order By: Relevance
“…The short-term effect of positive reappraisal could be helpful for youth experiencing difficulties in managing negative effects [16]. Studies have shown that having positive emotions helped people to come out of depression, following aftermath of any crisis in life [17] and that these positive emotions helped in providing a broad mind-set [2].…”
Section: Wwwjcdrnet Ramesh Mg Et Al Efficacy Of Meditation On Pmentioning
confidence: 99%
“…The short-term effect of positive reappraisal could be helpful for youth experiencing difficulties in managing negative effects [16]. Studies have shown that having positive emotions helped people to come out of depression, following aftermath of any crisis in life [17] and that these positive emotions helped in providing a broad mind-set [2].…”
Section: Wwwjcdrnet Ramesh Mg Et Al Efficacy Of Meditation On Pmentioning
confidence: 99%
“…As both these factors are associated with clinical depression and depressive symptoms in healthy subjects (Karg et al, 2011;Papageorgiou and Wells, 2004;Rood et al, 2010;Sharpley et al, 2014), we expected and confi rmed in our database that high ruminating S'-carriers showed a greater incidence of depressive symptoms. We propose that in combination, the stress vulnerability caused by carrying an S'-allele will be further exacerbated by the prolonging of stress responses caused by ruminative thinking .…”
Section: Discussionsupporting
confidence: 73%
“…In the current study, unless stated otherwise, rumination will be defi ned as a negative trait (brooding) while it is known to put the body in a state of long lasting cortisol levels even after the stressor disappeared (Zoccola and Dickerson, 2012). Complimentary evidence for the cognitive stress vulnerability that ruminative thinking poses can be found in the fact that it plays an important role in depression (Rood et al, 2010) and eating disorders (Birmingham and Firoz, 2006) and is a solid predictor for negative aff ect in healthy subjects (Roelofs et al, 2008). One of the few studies concerning rumination's relation to emotional eating even found that rumination was a mediator for the eff ect of daily stress on food intake among obese adults (Kubiak et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Localización anatómica de las áreas activadas en los s/C al escuchar la obra de Bach durante el estudio de IRMf circuito fronto-estriatal, que se ha relacionado con la anticipación musical 22 y el circuito del placer, 23 parece indispensable en la función gratificante para dar sentido a la escucha musical. 24 En cuanto al sesgo hacia emociones y pensamientos negativos, presente en los pacientes deprimidos, 25,26 éste podría corresponder al exceso de activación de la Default Mode Network (DMN) 27 que ya ha sido reportada hiperactiva en pacientes con depresión. [28][29][30] En la DMN se ha propuesto a la corteza cingulada posterior como responsable de los pensamientos autoreferenciales con sesgo negativo.…”
Section: Comparación Con Otras Publicacionesunclassified